The Possibility of Vice-Presidents’ Authority Arrangement in the 1945 Constitution through Constitutional Amendment - Fajar L. Suroso (Faculty of Law, Hasanuddin University, 2016)
The debate over the vice-presidents’ authority reappeared in the administration of President Jokowi after the “authority expansion of the Chief of Presidency Staff” and the case of “Rizal Ramli vs Jusuf Kalla”. This article is intended to provide arguments for the idea of some parties to organize more explicit and detailed the authority of vice-president in the 1945 Constitution. The idea arises from the absence of further arrangement on the authority of vice-president in the 1945 Constitution. This article is systematized into 3 (three) sub-theme; 1) the arrangement of the vice-presidents’ authority in the constitution for several countries; 2) The authority of the vice president according to the 1945 Constitution, and 3) New resultant and the possibility of 1945 Constitution amendment. The result revealed a number of interesting things; 1) the constitutions of other countries do not specify the authority of the vice-president and put the vice-president as a “spare tire” when the president is absent; 2) no new resultant about the position and authority of the vice-president so that theoretically is not reason enough to regulate in detail the authority of the vice-president through the 1945 Constitution amendment; 3) arrangement in detail in the authority of vice-president in the 1945 Constitution holds the potential to confuse the presidential system design as the 1945 Constitution. Therefore, the possibility of vice-presidents’ authority arrangement in the 1945 Constitution through amendment is very small, both in terms of momentum and the substance of issues.